Lebanon a history, 600-2011 - Harris, William W. (Studies in Middle Eastern history (New York, N.Y.), 2012)
The book explores the affairs of Mount Lebanon and its surrounds through fourteen centuries, beginning with the emergence of its Christian, Muslim and Islamic-derived communities between the sixth and eleventh centuries. Against this backdrop, it interprets the modern republic of Lebanon from Ottoman antecedents to present day crises